Turning Shy on a Winter's Day: Effects of Season on Personality and Stress Response in Microtus arvalis - Gracceva, Giulia; Herde, Antje; Groothuis, Ton G. G.; Koolhaas, Jaap M.; Palme, Rupert; Eccard, Jana A. (Ethology, 2014)
Gracceva G, Herde A, Groothuis TGG, Koolhaas JM, Palme R, Eccard JA. Turning Shy on a Winter's Day: Effects of Season on Personality and Stress Response in Microtus arvalis. Ethology . 2014;120(8):753-767.